2012
DOI: 10.1016/j.nlm.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment protects against the effects of chronic stress on cognitive and morphological measures of hippocampal integrity

Abstract: Chronic stress has detrimental effects on hippocampal integrity, while environmental enrichment (EE) has beneficial effects when initiated early in development. In this study, we investigated whether EE initiated in adulthood would mitigate chronic stress effects on cognitive function and hippocampal neuronal architecture, when EE started one week before chronic stress began, or two weeks after chronic stress onset. Adult male Sprague Dawley rats were chronically restrained (6h/d) or assigned as non-stressed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 99 publications
(127 reference statements)
7
60
0
Order By: Relevance
“…The reversal might involve adaptive mechanisms resulting from the mismatch between favorable EE conditions and adverse conditions in early life. These mechanisms may also involve epigenetic regulation of GR gene in the hippocampus, consistent with the idea that chronic stress and EE recruit similar pathways within the hippocampus (Hutchinson et al, 2012). Additional molecular pathways may also be involved.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The reversal might involve adaptive mechanisms resulting from the mismatch between favorable EE conditions and adverse conditions in early life. These mechanisms may also involve epigenetic regulation of GR gene in the hippocampus, consistent with the idea that chronic stress and EE recruit similar pathways within the hippocampus (Hutchinson et al, 2012). Additional molecular pathways may also be involved.…”
Section: Discussionsupporting
confidence: 71%
“…EE is a non-invasive and natural paradigm that increases the level of sensory, cognitive, and motor stimulation and promotes brain plasticity. It has been used to restore hippocampal integrity after chronic stress (Hutchinson et al, 2012) and may have some potential to counteract symptoms of psychopathologies and neurodegenerative diseases (Hannan, 2014;Nithianantharajah and Hannan, 2006). Our findings demonstrate that EE can reverse the effects of early traumatic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the long history of studies of the effects of enriched environmental conditions on neurophysiological characteristics and learning ability [13,[21][22][23]25], this study showed that keeping animals in enriched conditions promotes increases in movement activity, the development of exploratory behavior, and increases in emotional reactivity in situations of moderate stress in the open fi eld. The results provided evidence that mothers with chronic alcoholic liver disease give birth to offspring with nervous system impairments.…”
Section: Discussionmentioning
confidence: 82%
“…The whole brain and various of its morphological parameters have been shown to change when laboratory animals are placed in specially formulated enriched environments [32]. Enriched environments have positive effects on the state of cognitive functions in animals in health and after exposure to chronic stress [25]. The main inducers of such infl uences are changes in the expression of growth factors in the brains of animals, along with increases in neuro-and synaptogenesis [21,22].…”
mentioning
confidence: 99%